Comparison between minimal fluoroscopy and conventional approaches for visually guided laser balloon pulmonary vein isolation ablation. (4th June 2020) - Huang, Henry D.; Rodriguez, Jason M.; Serafini, Nicholas J.; Macias, Carlos; Winterfield, Jeffrey; Sharma, Parikshit S.; Larsen, Timothy; Krishnan, Kousik; Trohman, Richard G.
Abstract: Introduction: Although balloon‐based techniques, such as the laser balloon (LB) ablation have simplified pulmonary vein isolation (PVI), procedural fluoroscopy usage remains higher in comparison to radiofrequency PVI approaches due to limited 3‐dimensional mapping system integration. Methods: In this prospective study, 50 consecutive patients were randomly assigned in alternating fashion to a low fluoroscopy group (LFG; n = 25) or conventional fluoroscopy group (CFG; n = 25) and underwent de novo PVI procedures using visually guided LB technique. Results: There was no statistical difference in baseline characteristics or cross‐overs between treatment groups. Acute PVI was accomplished in all patients. Mean follow up was 318 ± 69 days. Clinical recurrence of atrial fibrillation after PVI was similar between groups (CFG: 19% vs LFG: 15%; P  = .72). Total fluoroscopy time was significantly lower in the LFG than the CFG (1.7 ± 1.4  vs 16.9 ± 5.9 minutes; P  < .001) despite similar total procedure duration (143 ± 22 vs 148 ± 22 minutes; P  = .42) and mean LA dwell time (63 ± 15 vs 59 ± 10 minutes; P  = .28). Mean dose area product was significantly lower in the LFG (181 ± 125 vs 1980 ± 750 μGym 2 ; P  < .001). Fluoroscopy usage after transseptal access was substantially lower in the LFG (0.63 ± 0.43 vs 11.70 ± 4.32 minutes; P  < .001). Complications rates were similar between both groups (4% vs 2%; P  = .57). Conclusions: This study demonstrates that LB PVI can be safely achieved using a novel low fluoroscopy protocol while also substantially reducing fluoroscopy usage and radiation exposure in comparison to conventional approaches for LB ablation.